The effect of reduction, trypsin digestion and de-glycosylation of salivary mucins in the inhibition of human immunodeficiency virus type 1 - Tsetse, Ellis CT (Department of Surgery, 2020)
In 2017, 36.7 million people worldwide were living with Human Immunodeficiency Virus (HIV) and of that total, 1.8 million people were new infections. Sub-Saharan Africa was recognized as the most afflicted regions worldwide accounting for 26 million people, 68%, living with HIV. The difficulty in fighting this epidemic has raised the urgent need for research exploring ways in which HIV transmission can be curbed worldwide. Our laboratory previously showed that crude saliva and purified salivary mucins (MUC5B and MUC7) inhibit HIV-1 infection in vitro. However, it is not known whether the specific arrangement of mucin carbohydrate residues is important for mucin interactions with HIV-1, or if the negative charge afforded by sialic acid and sulfated sugars allows binding to viral receptors. While giving some important insight into the mechanism of HIV inhibition, we hope that this study will determine the minimum peptide chain length and structure of a gel forming mucin that retains the anti-HIV activity. In addition, we aim to determine if the reduced salivary subunits and trypsin digested fragments retained this inhibitory activity against HIV-1. Saliva was collected and stirred overnight in 6M guanidine hydrochloride with 10mM Na2HPO4, 10mM EDTA, 1mM PMSF and 5mM NEM. Salivary mucins (MUC5B and MUC7) were purified using caesium chloride ultracentrifugation and separated on a Sepharose CL-4B column. Thereafter, mucin rich fractions were either reduced with 10mM dithiothreitol (DTT) or proteolytically digested with 0.25% trypsin. The resultant fractions were dialysed and freeze dried. Slot blots were used to determine the identity of the void volume (Vo) fractions and the included volume (Vi) fractions which were identified as MUC5B and MUC7 respectively. The Vo and Vi fractions were subjected to 4- 20% sodium dodecyl sulphate polyacrylamide gel (SDS-PAGE) to determine the size and mucin concentration. In addition, mucin oligosaccharides were enzymatically removed using the de-glycosylation kit (EDEGLY) purchased from Sigma Aldrich (UK). Following this, all mucin lyophilized aliquots were tested for cell cytotoxicity using an MTT assay. This was then followed by a neutralisation assay which uses HIV-1 env pseudo virus (DU422.1 and YU2 subtype C and subtype B respectively) and a luciferase reporter gene involving modified TZM-bl/JC cells was used to test the inhibitory activity of the test samples. Comparison of the anti-HIV activity of crude saliva, MUC5B and MUC7 against the DU422 virus showed that both crude and purified saliva indeed inhibits the infection of the DU422.1 pseudo-virus strain to TZM-bl/JC cells (Kruskal-Wallis, p=0.00025). MUC5B was more potent in inhibiting the DU422 virus as compared to crude saliva and MUC7 (MannWhitney U, p=0.0227 and p=0.0195 respectively). Furthermore, no difference was observed in inhibiting the DU422 virus by MUC7 and crude saliva (Mann-Whitney U, p=0.128). While the three cohort of samples did inhibit the YU2 pseudo virus (KruskalWallis, p=0.0078), MUC7 showed a higher inhibition compared to MUC5B and crude saliva (Mann-Whitney U, p=0.0341 and p=0.176 respectively). A significant difference in the inhibition of the YU2 virus was detected between MUC7 and crude saliva (MannWhitney U, p=0.0031). In addition, reduced and digested salivary fragments inhibited both viruses suggesting the possibility that even when the gel forming properties of mucins are compromised, mucins still retain their inhibitory activity. Interestingly, the removal of oligosaccharides showed MUC5B as the most potent mucin in the inhibition of both DU422 and the YU2 pseudo virus (Kruskal-Wallis, p=0.0312). Deglycosylated MUC7 displayed minimal inhibition against the YU2 and DU422 virus suggesting that oligosaccharides are important for maximal inhibition. Furthermore, this highlights that the mechanism through which mucins inhibit viruses involve glycans. In conclusion, the results of this study suggest that MUC5B can be harnessed and used as a core component of a microbicide which can be used to prevent HIV transmission. Its extensive glycosylation compared to MUC7 makes it a better candidate for this anti-HIV1 inhibitory activity.